What Is the Microbiome? A Description of a Social Network - van Praagh, J.B.; Havenga, Klaas (Clinics in Colon and Rectal Surgery, 2023)
The gut microbiome has coevolved with its hosts over the years, forming a complex and symbiotic relationship. It is formed by what we do, what we eat, where we live, and with whom we live. The microbiome is known to influence our health by training our immune system and providing nutrients for the human body. However, when the microbiome becomes out of balance and dysbiosis occurs, the microorganisms within can cause or contribute to diseases. This major influencer on our health is studied intensively, but it is unfortunately often overlooked by the surgeon and in surgical practice. Because of that, there is not much literature about the microbiome and its influence on surgical patients or procedures. However, there is evidence that it plays a major role, showing that it needs to be a topic of interest for the surgeon. This review is written to show the surgeon the importance of the microbiome and why it should be taken into consideration when preparing or treating patients.
Keywords: bacteria; microbiome; surgery; symbiosis; dysbiosis